2016
DOI: 10.3906/sag-1412-41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of the COL1A1 gene promoter –1997 G/T (rs1107946) andSp1 +1245 G/T (rs1800012) polymorphisms and keloid scars in a Jeddah population

Abstract: IntroductionKeloid scars are benign fibroproliferative cutaneous lesions resulting from the overproduction of all components of the healing process, including fibroblasts, collagen, elastin, and proteoglycans; they can occur following burn injuries, lacerations, abrasions, surgery, piercings, vaccinations, and even minor skin trauma. They are unique in humans, and especially in genetically susceptible individuals from nonwhite populations (1-3). It has been estimated that about 15%-20% of Blacks, Hispanics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this study, the expression changes of the m6A modification site of COL1A1 and the stability of COL1A1 mRNA were shown to mediate the regulatory effect of FTO on keloids. Previous study has demonstrated gene promoters showed a strong positive connection with the risk of keloid formation (14). Wang et al found that COL1A1 mediates the promotion of H19 on the proliferation and metastasis of skin fibroblasts (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the expression changes of the m6A modification site of COL1A1 and the stability of COL1A1 mRNA were shown to mediate the regulatory effect of FTO on keloids. Previous study has demonstrated gene promoters showed a strong positive connection with the risk of keloid formation (14). Wang et al found that COL1A1 mediates the promotion of H19 on the proliferation and metastasis of skin fibroblasts (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has demonstrated that COL1A1 can promote the formation of keloids since excessive collagen deposition is an essential characteristic of keloids. A Linjawi et al discovered that the COL1A1 −1,997 G/T (rs1107946) and Sp1 +1,245 G/T (rs1800012) gene promoters showed a strong positive connection with the risk of keloid formation ( 14 ). Wang et al found that COL1A1 mediates the promotion of H19 on the proliferation and metastasis of skin fibroblasts ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…MMP‐1 rs1799750 is known to increase the expression of MMP‐1 and is indicative of susceptibility to skin aging 50 . It has also been reported that the G allele of COL1A1 rs1107946 enhances the production of α1 chain of type I collagen, affects the balance with α2 chain, changes the quality of the collagen chain, and promotes keloid formation 51 . The hardness of dermal collagen fibers may affect facial recovery and flexibility after skin deformation due to facial expressions such as laughing, which may promote transient wrinkle formation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed when ECM proteins (such as pro-Col1A1) increased, the excessive scar fibrosis occurred [31]. Scars are characterized by excessive collagen deposition, particularly types I and III collagen [32]. …”
Section: Discussionmentioning
confidence: 99%